2018
DOI: 10.1016/s2542-5196(18)30237-7
|View full text |Cite
|
Sign up to set email alerts
|

Workers' health and productivity under occupational heat strain: a systematic review and meta-analysis

Abstract: Background Occupational heat strain (ie, the effect of environmental heat stress on the body) directly threatens workers' ability to live healthy and productive lives. We estimated the effects of occupational heat strain on workers' health and productivity outcomes. Methods Following PRISMA guidelines for this systematic review and meta-analysis, we searched PubMed and Embase from database inception to Feb 5, 2018, for relevant studies in any labour environment and at any level of occupational heat strain. No … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
262
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 320 publications
(276 citation statements)
references
References 116 publications
10
262
0
4
Order By: Relevance
“…Piece‐rate work increases the likelihood that a worker will experience heat‐related illness and even death, and while piece‐rate work was not associated with heat strain in our work, nor was heat strain associated with AKI, other studies document the association of heat strain and AKI. A meta‐analysis by Flouris et al found that 15% of workers who experience heat stress also experience AKI or kidney disease. Workers paid by the piece tend to be unauthorized immigrants with lower levels of education and English‐language skills .…”
Section: Discussionmentioning
confidence: 99%
“…Piece‐rate work increases the likelihood that a worker will experience heat‐related illness and even death, and while piece‐rate work was not associated with heat strain in our work, nor was heat strain associated with AKI, other studies document the association of heat strain and AKI. A meta‐analysis by Flouris et al found that 15% of workers who experience heat stress also experience AKI or kidney disease. Workers paid by the piece tend to be unauthorized immigrants with lower levels of education and English‐language skills .…”
Section: Discussionmentioning
confidence: 99%
“…Labour productivity loss estimates for every degree increase of WBGT beyond 24°C range from 0.8% to 5%. 38 Reduced labour productivity is often the first symptom of the health effects of heat, and, if not addressed, may lead to more severe health effects, such as heat exhaustion and heat stroke.…”
Section: Headline Finding: Higher Temperatures Continue Tomentioning
confidence: 99%
“…We quantify the productivity losses (reduction in available work time) that would occur if the international standard recommendations are enforced (ISO 1989, see 'Wet bulb globe temperature and derived indices'). If working people do not reduce their work as much, the losses would be less but at the expense of other effects on workers' well-being (Flouris et al 2018). These ISO recommendations apply to acclimatized workers; thus, they might be more appropriate for Southern European cities.…”
Section: Tablementioning
confidence: 99%
“…Also, future heat waves are very likely to be more frequent and longer-lasting (IPCC 2013), mainly as a direct consequence of the increase in mean temperatures (Schär, et al 2004;Fischer and Schär 2010). Those changes relate to increasing environmental heat exposure throughout the twenty-first century (Willett and Sherwood 2010;Zhao et al 2015;Knutson and Ploshay 2016;Coffel et al 2018;Li et al 2018;Matthews 2018) which in turn might have an effect on mortality, well-being and labour productivity (Dunne et al 2013;Kjellstrom et al 2018;Mora et al 2017;Flouris et al 2018;Levi et al 2018;Moda et al 2019). The combination of environmental heat exposure and internal heat production generated from metabolic processes results in heat stress (Xiang et al 2014).…”
Section: Introductionmentioning
confidence: 99%